PENGEMBANGAN GAME EDUKASI DENGAN TEMA TANAMAN UNTUK MENINGKATKAN KOGNITIF ANAK USIA 5–6 TAHUN DI TK NEGERI PEMBINA CIBADAK - Aswar Suwartini; Isti Rusdiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a plant-themed educational game to improve cognitive abilities of children aged 5–6 years at TK Negeri Pembina Cibadak. The background of this research is the limited use of interactive digital learning media that can stimulate early childhood cognitive development optimally. This study employed a Research and Development (R&D) method adapted from the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects were 20 children aged 5–6 years. Data were collected through observation, interviews, and cognitive assessment sheets. The results showed that the educational game was feasible and effective in improving children’s cognitive abilities, particularly in classification, problem-solving, and logical thinking related to plant themes. The findings indicate that plant-themed educational games can be an alternative interactive learning media to enhance early childhood cognitive development.